Pengaruh Penggunaan User Centered Pada Perancangan UI/UX Pada Model Aplikasi Penjualan Es Teler Berbasis Website - Mutiara Nurikhlimah; Ade Dwi Putra (Bulletin of Computer Science Research, 2026)
Abstract The rapid development of information technology encourages businesses to adapt by utilizing digital platforms, one of which is through e-commerce websites. The Es Teler El website is developed as a web-based sales platform that requires optimal User Interface and User Experience (UI/UX) design to provide convenience, ease of use, and efficiency in transaction processes. This study aims to design the UI/UX of the Es Teler El website using the User-Centered Design (UCD) method and to evaluate the usability level of the resulting prototype. The UCD method is implemented through four main stages: Understand Context of Use, Specify User Requirements, Design Solution, and Evaluate Design Against Requirements. Data collection was conducted through interviews with 20 respondents to identify user needs. The results of the needs analysis were then implemented into wireframe, mockup, and high-fidelity prototype designs using Figma. Usability evaluation was carried out using the System Usability Scale (SUS) method involving the same respondents through predefined testing scenarios. The results show that the Es Teler El website prototype achieved an SUS score of 82.5, which falls into the “Excellent” category (Grade A). This indicates that the design meets usability aspects, including ease of use, efficiency, and user satisfaction. Therefore, the application of the UCD method is proven to be effective in producing UI/UX designs that align with user needs and improve the quality of user experience in web-based culinary e-commerce platforms.